Resposta imune e capacidade de neutralização de anticorpos produzidos em ovinos jovens imunizados com veneno de Crotalus durissus terrificus nativo e irradiado com Cobalto 60 - Ferreira Júnior, Rui Seabra [UNESP]; do Nascimento, Nanci; Couto, Renata [UNESP]; Alves, Janaína Baptista; Meira, Domingos Alves [UNESP]; Barraviera, Benedito [UNESP] (My University, 2009)
The ELISA technique was used to evaluate and compare young ovine humoral immune response during crotalic antiserum production. Animals were clinically evaluated throughout this process, and the neutralizing capacity of antisera raised against natural (NV) and Cobalt-60 irradiated (IrV) venoms of Crotalus durissus terrificus (C.d.t.) was verified by means of in vitro challenges. Three groups of six animals each were used: G1 received NV; G2 was inoculated with IrV; and G3 was used as control. Animals received six immunizations during 84 days at 14-day intervals. ELISA of antibody profile showed significant difference (p<5%) between experimental groups (G1<G2). These results justify the use of gamma radiation to detoxify Crotalus durissus terrificus venom like alternative to antiserum production. The neutralizing capacity of antiserum raised against IrV was fivefold higher than that of antiserum raised against NV. Results showed a new possibility of using ovines to produce commercial crotalic antiserum, which may be employed in the treatment of human and animal envenomation. Production cost might be reduced by the subsequent utilization of hyperimmunized ovines as food.
Immune response and neutralization capacity of antibodies produced in young sheep immunized with Crotalus durissus terrificus native or Cobalt-60 irradiated venom
Keywords: Crotalic antiserum; Crotalus durissus terrificus; Hyperimmunization; Irradiation; Ovines; Animalia; Ovis; Ovis aries